Primary outcomes of combined cataract extraction technique with Ab-Interno trabeculectomy and endoscopic Cyclophotocoagulation in patients with primary open angle Glaucoma - Juan Carlos Izquierdo; Josefina Mejías; Laura Cañola-R; Natalia Agudelo; Bárbara Rubio (BMC Ophthalmology, 2020)
Abstract Background Glaucoma surgery have been developed to lower intraocular pressure in a less invasive manner than traditional glaucoma surgery. The purpose of this article is to determine the outcome of using combined phacoemulsification technique, ab-interno trabeculectomy dual blade and endoscopic cyclophotocoagulation (ECP) surgeries in patients with primary open angle glaucoma. Methods A retrospective case series was performed on 27 consecutive eyes with both primary open-angle glaucoma (POAG) and cataract; each eye was treated with combined phacoemulsification, ab-interno trabeculectomy-Kahook Dual Blade and Endocyclophotocoagulation at Instituto de ojos Oftalmosalud, Lima, Peru, between April 2017 and May 2017. Inclusion criteria: 1) Patients with uncontrolled mild to advanced POAG (according to Glaucoma Grading Scale HODAPP) 2) cataract condition 3) treatment with two or more glaucoma medications due to rapid progression in the visual fields (at least two in a short period of time). Intraocular pressure (IOP), best corrected visual acuity (BCVA) logMAR and number of glaucoma medications were recorded prior to the study, at day 1, week 1, and 1,3,6 and 9 months after surgery. Primary outcome measure was surgical success defined in terms of IOP < 14 mmHg either with no medications (complete success) or with medications (qualified success). Results A total of 27 eyes from 27 patients were included. The mean basal IOP was 17.0 ± 3.7 mmHg and postoperatively was 11.6 ± 1.9 mmHg and 11.4 ± 1.8 mmHg (P < 0.001) at 6 and 9 months respectively. Glaucoma medications decreased from 1.9 ± 1.4 to 0.56 ± 1.05 at 9 month follow-ups (P < 0.001). Preoperative best corrected visual acuity (BCVA) showed and improvement from 0.4 ± 0.4 LogMAR to 0.2 ± 0.4 logMAR at 9 months. The main complication was blood reflux intra-operatively (66.7%), which resolved without re-operation. The mean IOP was reduced by 32.9% from baseline and the surgical success was 92,6%, (complete success 70,3% and qualified success 29,6%) at 9 months. Conclusions In patients with POAG, combined treatment with phacoemulsification, ab-interno trabeculectomy and endoscopic cyclophotocoagulation effectively reduced IOP and glaucoma medication dependence.